High‐Field Detection of Biomarkers with Fast Field‐Cycling MRI: The Example of Zinc Sensing. Issue 35 (21st May 2019) - Bödenler, Markus; Malikidogo, Kyangwi P.; Morfin, Jean‐François; Aigner, Christoph Stefan; Tóth, Éva; Bonnet, Célia S.; Scharfetter, Hermann
Abstract: Many smart magnetic resonance imaging (MRI) probes provide response to a biomarker based on modulation of their rotational correlation time. The magnitude of such MRI signal changes is highly dependent on the magnetic field and the response decreases dramatically at high fields (>2 T). To overcome the loss of efficiency of responsive probes at high field, with fast‐field cycling magnetic resonance imaging (FFC‐MRI) we exploit field‐dependent information rather than the absolute difference in the relaxation rate measured in the absence and in the presence of the biomarker at a given imaging field. We report here the application of fast field‐cycling techniques combined with the use of a molecular probe for the detection of Zn 2+ to achieve 166 % MRI signal enhancement at 3 T, whereas the same agent provides no detectable response using conventional MRI. This approach can be generalized to any biomarker provided the detection is based on variation of the rotational motion of the probe. Abstract : Fast‐field cycling magnetic resonance imaging (FFC‐MRI) enables zinc detection at 3 T, whereas no detection is possible with the same contrast agent using classical MRI at this field. The derivative of the relaxation rate as a function of the field is used rather than the relaxation rate itself, opening a new way in molecular imaging for efficient biomarker detection.